2007
DOI: 10.1080/01635580701365076
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Tomato Powder Supplementation in the Prevention of Leiomyoma of the Oviduct in the Japanese Quail

Abstract: Spontaneous leiomyomas of the oviduct are common tumors of the Japanese Quail (Coturnix coturnix japonica), which makes it a good animal model for screening potential agents for testing in the prevention and treatment of human myoma uteri. We have previously reported a decreased incidence of leiomyomas in the oviduct of Japanese quail with lycopene supplementation. Although the major carotenoid in tomatoes is lycopene, tomatoes also contain other compounds, which may contribute to their health benefit. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
2
14
2
Order By: Relevance
“…Our null associations for UL risk in relation to carotenoids, including lycopene, agree with previous epidemiologic data on this association (36), but conflict with animal data indicating a protective effect of lycopene supplementation on leiomyoma in the Japanese quail (32,33). However, serum concentrations of vitamin A in the quail increased in response to lycopene supplementation (32,33), which suggests that the protective agent in both animal and human studies might be high serum concentrations of vitamin A as opposed to lycopene itself. It is unclear whether these animal data are relevant to well-nourished human populations in whom dietary vitamin A intake is not as strongly correlated with serum vitamin A concentrations (62)(63)(64), but this hypothesis could be tested directly in future studies.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our null associations for UL risk in relation to carotenoids, including lycopene, agree with previous epidemiologic data on this association (36), but conflict with animal data indicating a protective effect of lycopene supplementation on leiomyoma in the Japanese quail (32,33). However, serum concentrations of vitamin A in the quail increased in response to lycopene supplementation (32,33), which suggests that the protective agent in both animal and human studies might be high serum concentrations of vitamin A as opposed to lycopene itself. It is unclear whether these animal data are relevant to well-nourished human populations in whom dietary vitamin A intake is not as strongly correlated with serum vitamin A concentrations (62)(63)(64), but this hypothesis could be tested directly in future studies.…”
Section: Discussionsupporting
confidence: 56%
“…Another explanation for this finding is that the absorption and bioavailability of vitamin A from animal sources is greater than that from vegetable or synthetic sources (59)(60)(61). Our null associations for UL risk in relation to carotenoids, including lycopene, agree with previous epidemiologic data on this association (36), but conflict with animal data indicating a protective effect of lycopene supplementation on leiomyoma in the Japanese quail (32,33). However, serum concentrations of vitamin A in the quail increased in response to lycopene supplementation (32,33), which suggests that the protective agent in both animal and human studies might be high serum concentrations of vitamin A as opposed to lycopene itself.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Shahin et al (2007) in a case-control study in Turkey examined using Lycopene compounds and tomato powder in preventing of myoma in Japanese quail; results showed that using more antioxidant compounds such as tomato prevents uterine myoma that was not in agreement with our study. The reason of this contradiction may be the use of human samples instead of quail in our study (16). In a review study on etiology and pathogenesis of uterine myoma done by Gordon Flick et al (2003), consumption of meat, pork and other meat products increased uterine myoma while using antioxidants such as fruits and vegetables decreased it; this was not consistant with our study.…”
Section: Discussioncontrasting
confidence: 49%
“…In a similar study in America in 2008, there was found no relationship between the diet in general, high-fiber diet, soya and leiomyoma but in this study, drinking alcohols increased leiomyoma (15). In another study in 2007, there was a direct relationship between tomato powder and reduced uterine tube myoma in Japanese quail (16). Besides, in a research done in 1997, meat consumption increased the risk of leiomyoma incidence, but vegetable consumption decreased it (17).…”
Section: Introductionmentioning
confidence: 78%